Prediction of Land Cover Changes in Evaluation of Regional Spatial Planning in the Keduang Sub-Watershed, Wonogiri Regency - Ramadhan, Aditya; Bayuhasta, Damar Fauzan (PT. Pubsains Nur Cendekia, 2024)
River watersheds have an important function for water absorption for human life. The Pemudang sub-watershed is a national priority because its condition is increasingly critical due to land degradation. This research aims to carry out spatial modeling of land cover changes in 2031 in the Uangng Sub-watershed which will be compared with the 2011-2031 Regional Spatial Plan scenario. The method used uses the Cellular Automata-Markov Chain method. Based on predictions of land cover in 2031, agricultural areas dominate in the Uangng Sub-watershed covering an area of 14,783.4 ha (37.5%). Agricultural area according to the model in 2031 is estimated to increase by 97.5 ha. The difference between the 2031 model area and the region spatial plan is 5,168.9 ha, which means that the region spatial plan settlements are not expected to be able to accommodate future settlements. The forest area in the 2031 model is 12,351.6 ha, while in the region spatial plan it is 12,300.3 ha with an area difference of 51.2 ha. This shows that controlling the use of space in forests is not in accordance with the policies in the region spatial plan.